The effect of knowledge sharing behaviour in influencing knowledge-based economy - Ashari, H.; Jayasingam, S. (2014)
With the advent of the economy knowledge age, knowledge has become the fundamental means of wealth creation and prosperity and the most important driving force for business success. As a result, skilled workforce has been recognized as the engine of growth to support the knowledge-based economy and to ensure the permanence of innovative organizations. This article aims to provide an overview on the effects of knowledge sharing on knowledge economy by critically reviewing past literature published to date on knowledge sharing behaviour in highly competitive environments or in which knowledge has high commercial value due to the dilemma resulting from contradictory incentives to share or to withhold knowledge.